Activity Based Costing in Universities - Second Step of Calculation of Teaching Cost - Klaus-Rosińska, Agata; Kowalski, Michał Jerzy (Rachunek kosztów działań w szkołach wyższych - drugi etap kalkulacji kosztów kształcenia, 2011)
The article is a continuation of consideration contained in an article titled "Activity based costing - first step of calculation of teaching costs". The article describes information regarding the second step of the calculation according to the ABC, points to the problems encountered during project implementation and indicates further actions necessary to implement the activity based management (ABM).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 62-70
Keywords: activity-based costing; cost calculation; teaching costs